Plasmon–exciton polaritonic emission lifetime dynamics under strong coupling - Jurkšaitis Povilas; Anulytė Justina; Spalinskaitė Evita; Bužavaitė-Vertelienė Ernesta; Žičkus Vytautas; Banevičius Dovydas; Kazlauskas Karolis; Balevičius Zigmas (Nanophotonics)
In this study, we investigate the contribution of resonant and non-resonant excitation conditions on the polariton decay dynamics of strongly coupled rhodamine 6G (R6G) and surface plasmon polariton (SPP). We showed proof of strong coupling between SPP and R6G exciton from the dispersion relations measured by total internal reflection ellipsometry (TIRE). From these it was determined that the coupling strength reaches g ≈ 200 meV. Further fluorescence methods were employed to demonstrate the emission from the lower polariton branch (LP). The fluorescence lifetime and back focal plane imaging techniques were implemented to study radiative polariton decay, for resonant and non-resonant excitation conditions. Fluorescence decay measurements of plasmonic strong coupling regime showed considerably longer (ps) than expected lifetime values (fs). In our case the measured lifetimes cannot be explained without the influence of additional energy level in emission dynamics, such as incoherent transition from exciton reservoir to lower polaritonic branch. The fundamental understanding of coherent energy exchange dynamics has potential importance for development of quantum optical nanodevices, polaritonic lasers, polariton condensation.